Técnicas gráfico plásticas y la motricidad fina en niños de cinco años de la Institución Educativa Inicial N° 344 Mi Primer Aprendizaje, Punchana 2022 - Panduro Andrade, Tammy Christy (2024)
The central purpose of this research was to establish the relationship between the use of graphic-plastic techniques and the development of fine motor skills in five-year-old children belonging to the Initial Educational Institution No. 344 "My First Learning" in Punchana during the year. 2022. The methodological approach used in this study was correlational and cross[1]sectional in nature, characterized by a non-experimental design. The population under study was made up of 40 five-year-old children enrolled in the aforementioned educational institution, and census sampling was used for their selection. To collect the necessary data, observation was used as the main tool, supported by an observation guide specifically designed to record relevant information. In order to validate the effectiveness of these instruments, three professionals with experience in the research area participated. The results of the analysis revealed a Pearson coincidence coefficient between the variables of the graphic-plastic techniques and the level of development of fine motor skills in the children, which yielded a value of r=-0.095. This result indicates a low correlation between both variables, which leads to the conclusion that there is no significant relationship between the use of graphic-plastic techniques and the development of fine motor skills in five-year-old children in the context studied.